β-secretase inhibition prevents structural spine plasticity deficits in AppNL-G-F mice - Blume, Tanja; Filser, Severin; Sgobio, Carmelo; Peters, Finn; Neumann, Ulf; Shimshek, Derya; Saito, Takashi; Saido, Takaomi C.; Brendel, Matthias; Herms, Jochen (Frontiers in Aging Neuroscience, 2022)
All clinical BACE1-inhibitor trials for the treatment of Alzheimer's Disease (AD) have failed due to insufficient efficacy or side effects like worsening of cognitive symptoms. However, the scientific evidence to date suggests that BACE1-inhibition could be an effective preventative measure if applied prior to the accumulation of amyloid-beta (Aβ)-peptide and resultant impairment of synaptic function. Preclinical studies have associated BACE1-inhibition-induced cognitive deficits with decreased dendritic spine density. Therefore, we investigated dose-dependent effects of BACE1-inhibition on hippocampal dendritic spine dynamics in an APP knock-in mouse line for the first time. We conducted in vivo two-photon microscopy in the stratum oriens layer of hippocampal CA1 neurons in 3.5-month-old AppNL-G-FGFP-M mice over 6 weeks to monitor the effect of potential preventive treatment with a high and low dose of the BACE1-inhibitor NB-360 on dendritic spine dynamics. Structural spine plasticity was severely impaired in untreated AppNL-G-FGFP-M mice, although spines were not yet showing signs of degeneration. Prolonged high-dose BACE1-inhibition significantly enhanced spine formation, improving spine dynamics in the AD mouse model. We conclude that in an early AD stage characterized by low Aβ-accumulation and no irreversible spine loss, BACE1-inhibition could hold the progressive synapse loss and cognitive decline by improving structural spine dynamics.